WOMEN’ STRUGGLE IN SURVIVING THEIR LIVES AS SEEN ON THE NOVEL ENTITLED MARY BARTON BY ELIZABETH GASKEL (A FEMINISM STUDY) - Widyahening, Ch. Evy Tri (UNIVERSITAS SLAMET RIYADI, 2016)
The research is aimed to analyze the struggle of women, especially women from a loweconomy class, in surviving thei lives as seen on the novel entitled ‘Mary Barton’ by ElizabethGaskell based on a Feminism Study. Elizabeth Gaskell has written this novel in the 19th centurywhen the industrial revolution has happened in England. In analyzing this novel, the researcherused descriptive qualitative method. There were two kinds of data sources: the primary datasources and the secondary data sources. The primary data source was the novel entitled ‘MaryBarton’ by Elizabeth Gaskell. Then, the secondary data were books, internet sources, andresearch journals which were related with this topic. The data collecting in this research waslibrary research by summarizing, paraphrasing, and documenting the data. The technique ofdata analysis was interactive data analysis by Miles and Huberman. The result of the analysisshowed that the novel illustrated the struggle of women from a low economy class in survivingtheir lives in the 19th century in England. The condition of poverty has made them to bestronger in facing their lives and struggling to get a better life. Mary Barton, as a maincharacter, became a heroine from a lower class to struggle against their poverty life and she didit well. In 19th century in England, there were many women who struggled in many aspects oftheir lives, such as economic aspect, social aspect, law and justice aspect, aesthetic aspect, andpsychological aspect. It was one of the impact of Indrustrial revolution in England at that timewhich has changed many sectors of life for women. So, it can be concluded that the struggle ofwomen in the world especially in England has been happened for many years. In England, it hasbecame bigger when the industrial revolution happened. It has changed the condition of womenbecame better and better until now.Keywords: The struggle of women, A Feminism Study, Descriptive Qualitative